Carry-Over Rate of Aflatoxin B1 from Feed to Milk and its Impact on Haemato-Biochemical Parameters in Nili-Ravi Buffaloes (Bubalus bubalis) - Singh Bibyan, Ram; Kumar Saini, Ashwani; Pathak, Abhishek; Dhial, Kritika (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was undertaken to establish the transmission/carry-over rate of aflatoxin B1 (AFB1) from contaminated feed to AFM1 in milk of Nili-Ravi buffaloes. Twenty lactating buffaloes of almost similar weight (450-550 kg), lactation number (3-6) in early lactation (1-4 months) were divided into 5 treatments (T1 to T5), each having four replicates.The AFB1 concentration in feed of T1 to T5 was 0, 28, 56, 84 and 113 ppb, respectively. The average milk yield (kg/d) in treatments T1 to T5 during the collection period of experiment was 9.31±0.04, 9.24±0.04, 9.35±0.06, 9.42±0.07 and 9.42±0.05; and the total AFM1 excretion (µg/animal/5d) was 0.00±0.00, 19.20±0.04, 29.85±0.23, 39.00±0.14 and 47.74±0.14, respectively. The results revealed that the total AFM1 excretion increased with increasing concentration of AFB1 in feed. The average AFM1 concentration in T1 to T5 was 0.00±0.00, 0.41±0.01, 0.63±0.01, 0.83±0.01 and 1.01±0.01 ppb, respectively. The carry-over (%) of aflatoxin, i.e., transmission from feed to milk was 0.00, 0.76, 0.59, 0.51 and 0.48 in groups T1 to T5, respectively. The biochemical and haematological values in various treatment groups revealed that erythrocytes, PCV, haemoglobin and total protein content decreased (p